FRI0753-HPR Pain spread and pain intensity improve over time in women with fibromyalgia and chronic widespread pain. a 12 year follow up study. (15th June 2017) - Bergenheim, A; Johannesson, S; Nordeman, L; Joelsson, M; Mannerkorpi, K
Abstract : Background: In the Western world, the prevalence of chronic widespread pain (CWP) is about 10–15% while Fibromyalgia (FM) affects approximately 1–3% of the population. The ACR 1990 criteria define CWP as pain ≥3 months on the right and left side of the body, above and below the waist and axial skeletal pain. The 1990 criteria for FM are CWP in combination with pain in ≥11 of 18 tender points on manual palpation. Previous studies indicate that some patients with FM or CWP improve over time and the key to improvement is an important question in research and clinical practice. Objectives: The primary objective was to investigate the change of pain intensity and pain distribution after 12 years in 166 women with FM or CWP. The secondary objective was to compare baseline values of health related variables between patients who fulfilled the criteria for FM/CWP at the 12 year follow-up and patients who did not. Methods: In 2004, 166 women with FM or CWP participated in a randomized controlled trial in Sweden aiming to investigate effects of patient education and pool exercise. All 166 were invited to the present study in 2016 and 126 women (75%) participated. Data was collected by a standardized interview, questionnaires of health related aspects and a physical examination. Primary, within-group changes were calculated for pain distribution (Bergman's pain drawing 0–18) and the subscale for pain intensity (0–100 mm) included in the Fibromyalgia Impact Questionnaire (FIQ). Secondary, the group who fulfilled criteria for FM or CWP at follow-up were compared with the group who did not fulfil the criteria for FM or CWP, in overall health status (FIQ total), symptoms of stress (Stress and Crisis Inventory – SCI-93), walking capacity (6 min walk test), hand grip force (the Grippit) and self-reported physical activity (Leisure time physical activity instrument). Results: Primary: The 126 women with FM or CWP improved in pain distribution: mean values at baseline 12.9 (SD 3.4) vs follow-up 11.4 (SD 4.7), p<0.001 and pain intensity: mean values at baseline 69 mm (SD 18.5) vs follow-up 59 mm (SD 22), p<0.001. Secondary: 18% (n=23) of the 126 women did not fulfil the 1990 criteria for FM or CWP at follow-up, and they showed significantly better health status, lower symptoms of stress and higher walking capacity in 2004, than the women who still had FM or CWP at follow-up. Baseline mean values FM/CWP (n=123) vs Not FM/CWP (n=23): FIQ total 66 (SD 16) vs 55 (SD 15), p=0.006; SCI-93 80 (SD 23) vs 59 (SD 22), p<0.001; 6 min walk test 502 m (SD 86) vs 542 m (SD 80), p=0.028. No significant differences were found between the groups for baseline values of hand grip force and level of physical activity. Conclusions: This study showed that distribution and severity of pain improved during 12 years in women with FM or CWP. The group that improved most (18%), reported better health status, lower stress and had better walking capacity 12 years earlier. This knowledge is important for health care professionals to motivate the patients to apply a variety of strategies, including physical activity, to improve their health and symptoms. Disclosure of Interest: None declared